Methylphenidate and P300 in attention deficit hyperactivity disorder: A systematic review and meta-analysis - Barroso, Beatriz C. R. (2025)
Methylphenidate (MPH) is a stimulant medicine often used to treat attention deficit hyperactivity disorder (ADHD), as it may positively affect behaviour and brain activity. This work aims to systematise the current literature about the effects of MPH on the amplitude of P300 in individuals with ADHD. A systematic review and meta-analysis of empirical studies measuring P300 amplitude and comparing MPH administration to either a pre-MPH condition or healthy controls was conducted, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Our results revealed no overall (n = 13) significant differences between individuals diagnosed with ADHD and medicated with MPH and controls. Although, a moderation analysis by region found differences between both groups on frontal sites. When comparing the pre- and post-effects of MPH on the same individuals (n = 17), it appears that P300 amplitude tends to increase post-administration in central and posterior regions. In this second meta-analysis, a moderation by task revealed a larger effect size for go/no-go. In general, MPH was found to increase P300 amplitude in ADHD, somewhat normalising this aspect of their brain activity. The main limitations of the included studies are the insufficiently explained dosages and the skewness for male participants. Future research directions are discussed.